Ritmo das chuvas na Bacia do Pardo (SP/MG): reflexos na vazão dos rios Pardo e Mogi-Guaçu - Fontão, Pedro Augusto Breda [UNESP] (2014)
This is a research that searched in atmospheric dynamics, and weather types associated with it, the regional understanding of the temporal and spatial distribution of rainfall and its impact on water flow, from its genesis in the basin of Pardo, inserted in the northeastern part of the state of São Paulo and southern / southwest Minas Gerais. In this area, were collected, analyzed and selected rainfall data, allowing elect a homogeneous time series of data (1967-1994) that included the best spatial distribution in the compartments of the basin. After this procedure, traditional statistical techniques that allow to describe the chronological and spatial behavior of the rains, and elect standard years representative of extreme conditions (wet and dry years) and the standard were applied in the region, having chosen the years 1983 (wet), 1984 (dry) and 1989 (standard). These years were detailed daily level through the rhythmic analysis, a procedure that allowed visualization of the weather systems that were active in the region. The starting point was major flood episodes (spikes) and droughts to analyze the rhythmic sequences preceding such phenomena in the basin in order to understand its genesis and reflections generated in the fluid flow analysis of selected points. The results were described and synthesized through maps, cartograms, graphs and charts that helped a lot in the analyzes, interpretations and judgments about the subject matter